UJI PERBANDINGAN MEDIA TANAM MENGGUNAKAN LIMBAH PADAT PABRIK KARET PADA PEMBIBITAN TANAMAN KAKAO (Theobrama cacaoL) - di, Wahyu (Menara Ilmu, 2018)
Cocoa plant was a plantation commodity that had high economic value. Until now, farmershad not much interest in making cocoa as the main plant in the field of plantation due to lackof knowledge about technical cultivation.The purpose of this research was to determine theeffect of planting media comparison using solid waste rubber in planting breeding cocoa. Thisresearch was conducted in Pebaun Hilir Village, Kuantan Mudik district, Kuantan SingingiRegency. The research was conducted for 4 months starting from August to November 2017.The design used in this research is non factorial Random Group Design (RAK), that wasplanting media of solid waste rubber factory consisted of 4 treatment levels, repeated as manyas 3 replications so that 12 units of experiment were obtained. Each experimental unitconsisted of 4 plants, 3 of which were used as sample plants. The treatment was as follows: S0:Soil PMK (Control), S1: 1: 3 (soil: solid waste rubber factory), S2: 2: 2 (soil: solid wasterubber factory), S3: 3: 1 (soil: solid waste rubber factory). The observational data wereanalyzed statistically and continued with the Brightness Advanced Test (BNJ) at 5% level. Theparameters observed were: Plant height (cm), stem diameter (cm), number of leaves (strands),leaf area (cm). The comparison treatment of planting media using solid waste rubber factoryhad an effect on observation parameter of leaf area with mean of 249 cm2 with best treatment1: 3 (soil: solid waste rubber factory).Keywords: Comparison of planting media, growth of cocoa seedlings